Rituximab and hypogammaglobulinemia in the setting of ABO-incompatible kidney transplantation - Hamza Naciri Bennani; Zhyiar Abdulraham; Bénédicte Puissant-Lubrano; Asma Allal; Lionel Rostaing (Society of Diabetic Nephropathy Prevention, 2018)
Background: ABO-incompatible (ABOi) kidney transplantation can be achieved by desensitizing the recipient using apheresis plus rituximab-based immunosuppression. Objectives: We sought to ascertain the factors that contributed to low immunoglobulin levels at post-ABOi kidney transplantation. Patients and Methods: This single-center study included 43 ABO-i kidney-transplant recipients desensitized with rituximab-based therapy. Posttransplant immunoglobulin levels (IgG, IgA, and IgM) were prospectively monitored within 2 years. If severe hypogammaglobulinemia occurred, i.e., IgG levels <4 g/L, patients received polyvalent immunoglobulin (IVIg substitution). Results: Within 1-year posttransplantation, 25% of patients experienced at least once severe hypogammaglobulinemia. On D -30 (pre-transplantation), IgG, IgA, and IgM levels were within normal ranges: 10 ± 4.4, 1.9 ± 1.2, and 0.8± 0.5 g/L, respectively. IgG levels were significantly decreased at D0 (4.2 ± 3.8 g/L) compared to D-30. At D15, IgG levels did not significantly differ from those on D0 or D -30. Conversely, beyond month-1 posttransplant IgG levels were within normal ranges and were significantly higher than levels measured on D0. Within three months posttransplantation, 11 patients required IVIg because IgG levels were <4 g/L (IVIg+ group). When these patients were compared with those that did not receive IVIg within 3 months posttransplantation (IVIg- group), IgG levels were similar at D -30 in both groups. Conversely, at D0, IgG levels were significantly lower in the Ig+ group (2.4 ± 2 vs. 5.5± 4.2 g/L; P = 0.009); t he d ifference remained significant until D15 posttransplantation (Ig+: 3.4 ± 1.7, Ig-: 6.6 ± 2 g/L; P = 0.0002). There was no statistical difference between the two groups after D15. Infectious complications did not significantly vary between patients with or without hypogammaglobulinemia. Conclusions: We conclude that hypogammaglobulinemia occurred frequently after ABOincompatible kidney transplantation but did not cause more infectious complications.